Drinking and driving in Vietnam: prevalence, and public knowledge, attitudes, and practices. (7th October 2012) - Bachani, AM; Cuong, P; Zamamiri, Y; Quang, LN; Passmore, J; Nguyen, PN; Hyder, AA
Abstract : Background: Injuries a leading cause of death in Vietnam and road traffic crashes account for half of those deaths. Alcohol involvement in road traffic crashes remains high. Aims/Objectives/Purpose: This study aims to illustrate the prevalence of drinking and driving, and knowledge, attitudes and practices (KAP) related to it in three provinces in Vietnam. Methods: Observational studies to establish the prevalence of drinking and driving were carried out in collaboration with the local police. Roadside KAP surveys were also conducted in all three provinces. Participants were asked questions about awareness of traffic laws, and their own alcohol use and driving practices. Results/Outcomes: The prevalence of drinking and driving remains high, ranging from 5% to 52% for the period of November 2010 to July 2011. 4 rounds of KAP interviews conducted in 2011 show that almost all the respondents of the increased risk of a road traffic crash due to alcohol consumption. However, a significant proportion (45%) reported drinking and driving in the past. Most common reasons cited for this practice were: 'feeling conscious', no alternative, and being near home or work. Preferred alternatives to drinking and driving, if available, were: leaving with a non-drinker, resting until 'feeling conscious' and drinking less. Knowledge on drink driving legislation remains low (13–29%). Significance/Contribution to the Field: The results of this study highlight the need to increase awareness of legislation against drinking and driving in Vietnam, as well as the need to develop programmes that serve as alternatives to address this problem in Vietnam.